Development of a scientific attitude measurement instrument for Dharmacariya department students at STABN using the Fishbein and Ajzen model - Syah, Rahmat; Darmawan, Daddy; Syamsuddin, Syaiful (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
This study applies the Fishbein and Ajzen model to develop a Scientific Attitude Measurement Instrument for Students, focusing on attitudes, beliefs, and intentions towards scientific behaviors. The quantitative research employs an instrument development method, initially constructing dimensions reflecting various scientific attitudes such as attitudes towards the scientific method, collaboration, openness to knowledge, criticality, respect, honesty, independence, and interest in data analysis. The instrument measures students' scientific attitudes across three main dimensions: attitude, subjective norms, and behavioral control, aligning with the Fishbein and Ajzen model. It covers key aspects like attitudes towards the scientific method, emphasizing rigorous approaches like Popper's Falsification concept, and the importance of social interaction in scientific collaboration. Validity and reliability analyses confirm the instrument's adherence to high-quality standards, making it relevant for assessing scientific attitudes and contributing to educational quality and student development in science. It provides a comprehensive view of students' perceptions and responses to scientific attitudes. Factor Loadings in the Rotated Component Matrix, with loadings above 0.50, indicate a strong correlation within the model. Cronbach's Alpha values range from 0.922 to 0.941, ensuring internal consistency and reliability. Exploratory Factor Analysis with student participants established the construct's validity and reliability, with a Kaiser-Meyer-Olkin (KMO) value of 0.747, indicating suitability for factor analysis. Most items showed high analytical validity, but items B22 and B13 require further review or adjustment.